Disclosure of Environmental Matters – Galp Energy - Azevedo, Graça; Oliveira, Jonas; Castro, Andreia (Journal of Environmental Accounting and Management, 2026)
There is a growing number of companies expressing social concerns where environmental worries are also included. Even before legal obligation of environmental disclosures, companies already used to adopt an active stance to safeguard their reputation. However, risk events may have negative impacts on companies’ legitimacy, making it necessary to implement strategies to repair/recover the damaged reputation. This study analyses the annual reports from 2001 to 2011 of the largest Por-tuguese oil company - Galp Energia - in the view of the occurrence of negative events, which, consequently, may have affected the company’s reputation. Empirically, legitimacy theory can explain the implementation of strategies to repair reputation. Within this context, most of the existing research is based on common-law countries, with little literature grounded on code-law countries, such as Portugal. Findings have shown that Galp Energia has great concerns about the external perception of society. The company acts immediately after risk events, implementing strategies to minimise the risk impact, especially through the use of corrective actions.